Angels and the order of heaven in medieval and Renaissance Italy - Gill, Meredith J. (Cambridge University Press, 2014)
Pure act: Medieval angelology and Dante's angels : Tongues of angels ; Dante and the scholastics ; The Divine Comedy -- Wings: Celestial visions in the later middle ages and Renaissance : Imagining heaven ; The nine orders: Padua, Riofreddo, and Rome ; The assumption and coronation of the virgin ; The communion of the blessed and the beatific vision -- Bodies and voices: Annunciation and heavenly harmonies :Ave Maria ; "A sound of tumult like the sounds of a host": the music of angels ; Jacob's ladder -- Contemplation: Angelic witness and empathy : The bread of angels ; Tobias and the angel ; Raphael transfigured -- Clouds and the fall: Rebellion, salvation, and reform : The fall of the rebel angels: Rome, Siena, and Caprarola ; Demons and artists